Role of Birds on Population Control of Destructive Insects - Dewi M Prawiradilaga (Media Konservasi, 1990)
Approximately 331 species of birds or 67% of the total number of buds on Java island are primary and secondary insectivores. These buds were found to feed on 14 orders of insects (72%) which are potential as crop destructives. The orders of Coleoptera, Lepidoptera and of Orthoptera were eaten by more than 100 birds species. In order to promote the use of birds to control destructive- insect population, it is important to study the bio-ecology of insectivorous buds in details.